Ответы и объяснения

Лучший Ответ!
2013-06-07T17:14:19+04:00

1)a)\frac{a^2+6a+9}{a+3}=\frac{(a+3)^2}{a+3}=a+3=-4.7+3=-1.7

   б)\frac{15x^2-5xy}{9x^2-y^2}=\frac{5x(3x-y)}{(3x-y)(3x+y)}=\frac{5x}{3x+y}=\frac{5*(-1)}{3*(-1)+4}=-5

 

2)a)(2b+3a)(3a-2b)=(3a+2b)(3a-2b)=(3a)^2-(2b)^2=9a^2-4b^2

    б)3a(a-3)-(a-4)^2=3a^2-9a-(a^2-8a+16)=\\=3a^2-9a-a^2+8a-16=2a^2-a-16

 

3)a)3a-3b-c(a-b) =3(a-b)-c(a-b)=(a-b)(3-c)

    б)a^4-a^3-4a+4=a^3(a-1)-4(a-1)=(a-1)(a^3-4)

    в)25b^2-(5-b)^2=(5b)^2-(5-b)^2=(5b-(5-b))(5b+(5-b)=\\=(6b-5)(4b+5)

 

4)y=-\frac{1}{5}x+3

a)x=-5;\ \ \ \ y=-\frac{1}{5}*(-5)+3=4

б)y=-2;\\ -2=-\frac{1}{5}x+3\\\frac{x}{5}=5\\x=25